THE ROLE OF THE CITY OF KUVA IN THE URBAN CIVILIZATION OF THE FERGANA VALLEY - Alisher Axmadjonovich Aloxunov; Tashmatov Bahtiyor Davlataliyevich (Sciental Journals Publishing, 2025)
This article analyzes the archaeological study of the city of Kuva in three distinct stages. It covers the initial observations beginning in 1916, the extensive archaeological expeditions of the 1950s–1990s, and the systematic scientific investigations conducted from the 1990s to the present. Special attention is given to the 2022 excavations carried out in the ark area of the Kuva Shahristan by researchers and students of Fergana State University. These excavations revealed three main construction phases, reflecting social, architectural, and cultural transformations beginning in the Qarakhanid period. The article also highlights the historical and cultural significance of Kuva within the broader context of the Fergana Valley and Central Asian civilization. It serves as an important resource for reassessing, preserving, and promoting the archaeological heritage of Kuva.
Keywords: Kuva, Fergana Valley, archaeology, urbanism, Qarakhanid period, ark, shahristan, defensive wall, Buddhist temple, archaeological research, cultural layer, Central Asia, civilizational heritage.